(untitled) (Journal of Forestry, 2024)
Global climate change causes the reduction of tree growth and spread of European beech (Fagus sylvatica L.) forests, thus indicating the need to preserve tree abundance due to the changes that have occurred. The comparison of beech seedlings from various provenances in southeast and central Europe was carried out based on the dimensions of root collar diameter and height to select the proper starting material that would reduce the negative consequences of the climate. There have been statistically significant differences in root collar diameter and height between various seedlings tested in European provenances. Clear differentiation was recorded between European countries in the growth performances of one-year-old and two-year-old seedlings of F. sylvatica based on the nursery test. The study’s results indicate the potential for producing adaptable beech reproductive material from various European provenances. This finding lays the groundwork for future precise analyses that aim to select provenances tolerant to changing climate conditions.